Studi Konten Analisis : Analisis Kecenderungan Dan Tren Riset Pendidikan Untuk Mata Pelajaran Fisika Di Indonesia - Rosa Safirotun Nabilah; Jumadi Jumadi (Postgraduate, University of Mataram, 2022)
Physics educational research trends are always changing from time to time. This change follows the phenomenon of educational problems that are developing in the field. The current study is a content analysis of research to analyze the trends of physics educational research that was published between the years of 2018 and 2021, visualize physics educational research trends and how Indonesian researchers contribute to physics educational research. This research was reached through the Journal of Research in Science Education (JPPIPA). Data obtained is 48 data and taken with